Future challenges in Rabbit Nutrition (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Rabbit breeding, although being a small sector of animal husbandry, is widespread in many areas of the world, as the rabbit is intended both for food (meat) and not food (fur) purposes. The rabbit production chain has to face various problems, mainly concerning animal health and product quality. To overcome these issues, studies using a multidisciplinary approach addressing aspects of the rabbit nutrition and feeding, with a direct impact on the rabbit farming, welfare, health, and meat quality are particularly appreciated and requested by the scientific community. This book is composed of four original papers and one review focused on different nutritional approaches. In particular a phyto-additive (thyme essential oil) and a rabbit-derived bacteriocin-producing strain (Enterococcus faecium CCM7420) with probiotic properties were investigated as new feed additives, while two types of insect fats were studied, in order to understand their effects as dietary replacements for soybean oil and their in vitro antimicrobial activities as alternative raw materials. Results collected in this book will be of particular interest for farmers and animal nutritionists working in the rabbit breeding sector